Assessment of the control measures for category A diseases of Animal Health Law: Contagious Bovine Pleuropneumonia. (21st January 2022) - ,; Nielsen, Søren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, José Luis; Gortázar, Christian; Herskin, Mette; Michel, Virginie; et al.
Abstract: EFSA received a mandate from the European Commission to assess the effectiveness of some of the control measures against diseases included in the Category A list according to Regulation (EU) 2016/429 on transmissible animal diseases ('Animal Health Law'). This opinion belongs to a series of opinions where these control measures will be assessed, with this opinion covering the assessment of control measures for Contagious Bovine Pleuropneumonia (CBPP). In this opinion, EFSA and the AHAW Panel of experts review the effectiveness of: (i) clinical and laboratory sampling procedures, (ii) monitoring period, (iii) the minimum radius of the protection and surveillance zones, and (iv) the minimum length of time the measures should be applied in these zones. The general methodology used for this series of opinions has been published elsewhere. Several scenarios for which these control measures had to be assessed were designed and agreed prior to the start of the assessment. Different clinical and laboratory sampling procedures are proposed depending on the scenarios considered. The monitoring period of 45 days was assessed as not effective and at least 90 days (3 months) is recommended in affected areas where high awareness is expected; when the index case occurs in an area where the awareness is low the monitoring period should be at least 180 days (6 months). Since transmission kernels do not exist and data to estimate transmission kernels are not available, the effectiveness of surveillance and protection zones for CBPP was based on expert knowledge. A surveillance zone of 3 km was considered effective, while a protection zone including establishments adjacent to affected ones is recommended. Recommendations, provided for each of the scenarios assessed, aim to support the European Commission in the drafting of further pieces of legislation, as well as for plausible ad hoc requests in relation to CBPP.